The EPPO/OLAF compendium of national procedures: Hungary - Hauck, Pierre; Schneider, Jan-Martin; Justus Liebig University Giessen (My University, 2025)
This Hungarian EPPO/OLAF volume focuses on criminal and administrative investigations in Hungary. As Hungary is a non-participating Member State to the EPPO, the EPPO chapter of this book discusses the relations between the EPPO countries and the Hungarian Prosecution Offices under a Working Arrangement as well as the rules of the Hungarian Prosecution Offices when investigating EU fraud and financial crime offences. It covers the material collected, co-operation with the Hungarian judicial authorities, criminal investigations into PIF-offences and compliance with the EPPO-Regulation. This volume also deals with the impact of OLAF investigations in Hungary and their significance for the Hungarian criminal justice system.
Keywords: ddc:340; ddc:320